2006
DOI: 10.1124/jpet.106.105015
|View full text |Cite
|
Sign up to set email alerts
|

High-Glucose-Altered Endothelial Cell Function Involves Both Disruption of Cell-to-Cell Connection and Enhancement of Force Development

Abstract: Vascular endothelial cells (ECs), which regulate vascular tonus, serve as a barrier at the interface of vascular tissue. It is generally believed that alteration of this barrier is correlated with diabetic complications; however, a detailed mechanism has not been elucidated. This study examined alteration of bovine arterial EC functions stimulated by a thromboxane A 2 analog (9,11-dideoxy-11␣,9␣-epoxymethano prostaglandin F 2␣ ; U46619) under normal and high-glucose (HG) conditions. U46619 treatment increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…It was recently reported that HG treatment enhances rho kinase activity via increases in rho A level in diabetic aorta (Akiyama et al, 2008). We suggested previously that HG-induced vascular endothelial cell dysfunctions participate in glucosedependent rho kinase activation (Nobe et al, 2006). A similar relationship between glucose and rho kinase was predicted with respect to the diabetic bladder smooth muscle dysfunction under HG conditions; however, a critical target of the enhanced extracellular glucose in relation to rho kinase activity is unknown.…”
Section: Discussionmentioning
confidence: 51%
“…It was recently reported that HG treatment enhances rho kinase activity via increases in rho A level in diabetic aorta (Akiyama et al, 2008). We suggested previously that HG-induced vascular endothelial cell dysfunctions participate in glucosedependent rho kinase activation (Nobe et al, 2006). A similar relationship between glucose and rho kinase was predicted with respect to the diabetic bladder smooth muscle dysfunction under HG conditions; however, a critical target of the enhanced extracellular glucose in relation to rho kinase activity is unknown.…”
Section: Discussionmentioning
confidence: 51%
“…On the other hand, we found that the disruption of EC‐EC tight confluent connectivity and TEER reduction were induced 72 hours after exposure to HGC . The reason for this finding could be that disrupted calcium dependence of EC‐EC connections via VE‐cadherin, morphological rearrangement, and paracellular gap formation was induced after exposure to HGC . The other possible mechanisms include the previously reported protein kinase C elevation and focal adhesion kinase phosphorylation impairment in HGC, which in turn can lead to deformed actin alignment .…”
Section: Discussionmentioning
confidence: 64%
“…17,50 The reason for this finding could be that disrupted calcium dependence of EC-EC connections via VE-cadherin, morphological rearrangement, and paracellular gap formation was induced after exposure to HGC. 51 The other possible mechanisms include the previously reported protein kinase C elevation and focal adhesion kinase phosphorylation impairment in HGC, which in turn can lead to deformed actin alignment. 52 In line with previous studies, we showed an enhanced expression of both VE-cadherin and ZO-1 at all-time points (especially at 72 hours) in the cells under HGC.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular hyperpermeability is one of the manifestations of endothelial dysfunction [1]. Evidence demonstrated that endothelial dysfunction is recognized as initial step in the atherosclerotic process and is well advanced in diabetes [2].…”
Section: Introductionmentioning
confidence: 99%